2017
DOI: 10.1097/pas.0000000000000962
|View full text |Cite
|
Sign up to set email alerts
|

Toward Biological Subtyping of Papillary Renal Cell Carcinoma With Clinical Implications Through Histologic, Immunohistochemical, and Molecular Analysis

Abstract: Papillary renal cell carcinoma (PRCC) has 2 histologic subtypes. Almost half of the cases fail to meet all morphologic criteria for either type, hence are characterized as PRCC not otherwise specified (NOS). There are yet no markers to resolve the PRCC NOS category. Accurate classification can better guide the management of these patients. In our previous PRCC study we identified markers that can distinguish between the subtypes. A PRCC patient cohort of 108 cases was selected for the current study. A panel of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 46 publications
2
69
1
2
Order By: Relevance
“…Additionally, the tumors demonstrated diffuse strong staining with ABCC2 (Fig. C) as we have previously described in the PRCC2 subtype (Saleeb et al ., ). Taken together, the morphology, immunostaining pattern, and molecular analyses show that CAKI‐2 can serve as a representative model for PRCC2.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Additionally, the tumors demonstrated diffuse strong staining with ABCC2 (Fig. C) as we have previously described in the PRCC2 subtype (Saleeb et al ., ). Taken together, the morphology, immunostaining pattern, and molecular analyses show that CAKI‐2 can serve as a representative model for PRCC2.…”
Section: Resultsmentioning
confidence: 97%
“…recent review on RCC cell lines describing multiple evidence linking CAKI‐2 to PRCC (Brodaczewska et al ., ). Additionally, CAKI‐2 harbors chromosome 8 aberrations, which has also been described in PRCC2 (Furge et al ., ; Saleeb et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…P‐RCCs are a highly heterogeneous group of RCCs, traditionally divided into types 1 and 2. However, an increasing number of recent studies showed that P‐RCC is more diverse than previously thought . It seems that these tumours are composed of different subtypes of RCC sharing similar architectural growth pattern, but demonstrating variable immunoprofile and molecular genetic features.…”
Section: Discussionmentioning
confidence: 97%
“…Papillary renal cell carcinoma (pRCC) represents a heterogeneous group of tumors that differ clinically, histologically, genetically, immunohistochemically, and also with regard to prognosis [1][2][3][4][5][6]. In a considerable fraction of pRCC tumors, it remains challenging to histopathologically classify 1 of the 2 official WHO 2016 subtypes (pRCC type 1 and 2).…”
Section: Introductionmentioning
confidence: 99%